2021
DOI: 10.1088/1674-1056/abe92a
|View full text |Cite
|
Sign up to set email alerts
|

Phase-shift interferometry measured transmission matrix of turbid medium: Three-step phase-shifting interference better than four-step one

Abstract: Transmission matrix (TM) is an important tool for controlling light focusing, imaging, and communication through turbid media. It can be measured by 3-step (TM3) or 4-step (TM4) phase-shifting interference, but the similarities and differences of the transmission matrices obtained by the two methods are rarely reported. Therefore, we make a quantitative comparison of the peak light intensity, signal-to-noise ratio, and average background of 24 × 24 = 576 focal points between paired samples (TM3-TM4) through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The results are shown in Table 1 and Figure 4. It can be found that the average prediction accuracy of the information transmission interference of the mobile communication system in this model is 96.477%, while the average prediction accuracy of the information transmission interference of the mobile communication system in ref [4] is 87.202%, which shows that this model can reduce the prediction error of the information transmission of the mobile communication system, improve the information transmission effect of the mobile communication system, and has obvious advantages.…”
Section: Results Analysismentioning
confidence: 85%
See 2 more Smart Citations
“…The results are shown in Table 1 and Figure 4. It can be found that the average prediction accuracy of the information transmission interference of the mobile communication system in this model is 96.477%, while the average prediction accuracy of the information transmission interference of the mobile communication system in ref [4] is 87.202%, which shows that this model can reduce the prediction error of the information transmission of the mobile communication system, improve the information transmission effect of the mobile communication system, and has obvious advantages.…”
Section: Results Analysismentioning
confidence: 85%
“…The result is shown in Figure 3. In order to further verify the superiority of DM in information transmission interference prediction of mobile communication system, the ref [4] method is selected for comparative testing in the same experimental environment. The results are shown in Table 1 and Figure 4.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation